The Determinants of Capital Structure Decisions: Evidence from Chinese Listed Companies - Vijayakumaran, S.; Vijayakumaran, R. (Asian Journal of Finance & Accounting, 2018)
In this paper, we examine the determinants of leverage in the context of China using a sample of 1844 Chinese non-financial firms over the period 2003 to 2010. This study shows that the average leverage ratio of Chinese listed firms is similar to those observed in other developing countries. The study also finds thatsize, tangibility, volatility and firm age are positively and significantly associated with leverage. Firm’s profitability has statistically significant negative impact on leverage. Furthermore, we find that firm size, profitability, tangibility, volatility and firm age are the robust determinants of leverage of Chinese listed firms.
Keywords: Capital Structure; Leverage; firm size; profitability